Instant Noodle Intake and Dietary Patterns Are Associated with Distinct Cardiometabolic Risk Factors in Korea. Issue 8 (25th June 2014) - Shin, Hyun Joon; Cho, Eunyoung; Lee, Hae-Jeung; Fung, Teresa T.; Rimm, Eric; Rosner, Bernard; Manson, JoAnn E.; Wheelan, Kevin; Hu, Frank B.
Abstract: The consumption of instant noodles is relatively high in Asian populations. It is unclear whether a higher intake of instant noodles is associated with cardiometabolic risk independent of overall dietary patterns. We therefore investigated the association using the Korean National Health and Nutrition Examination Survey IV 2007–2009, a nationally representative cross-sectional survey of the Korean population with a clustered, multistage, stratified, and rolling sampling design. A total of 10, 711 adults (54.5% women) 19–64 y of age were analyzed, with adjustment for sampling design complexity. Diet was assessed by using a 63-item food-frequency questionnaire. We identified 2 major dietary patterns with the use of principal components analysis: the "traditional dietary pattern" (TP), rich in rice, fish, vegetables, fruit, and potatoes, and the "meat and fast-food pattern" (MP), with less rice intake but rich in meat, soda, fried food, and fast food including instant noodles. The highest MP quintile was associated with increased prevalence of abdominal obesity (OR: 1.41; 95% CI: 1.05, 1.90), LDL cholesterol ≥130 mg/dL (1.3 g/L) (OR: 1.57, 95% CI 1.26, 1.95), decreased prevalence of low HDL cholesterol (OR: 0.65; 95% CI: 0.53, 0.80), and high triglycerides [≥150 mg/dL (1.5 g/L); OR: 0.73; 95% CI: 0.57, 0.93]. The highest quintile for the TP was associated with decreased prevalence of elevated blood pressure (OR: 0.73; 95% CI: 0.59, 0.90) and marginally lower trends for abdominal obesity (OR: 0.76; 95% CI: 0.58, 0.98; P- trend = 0.06), but neither of the dietary patterns was associated with prevalence of metabolic syndrome. The consumption of instant noodles ≥2 times/wk was associated with a higher prevalence of metabolic syndrome (OR: 1.68; 95% CI: 1.10, 2.55) in women but not in men (OR: 0.93; 95% CI: 0.58, 1.49; P- interaction = 0.04). The 2 major dietary patterns were associated with distinct cardiometabolic risk factors. The consumption of instant noodles was associated with increased prevalence of metabolic syndrome in women, independent of major dietary patterns.